A Molecular Approach to Manganese Nitride Acting as a High Performance Electrocatalyst in the Oxygen Evolution Reaction. (18th December 2017) - Walter, Carsten; Menezes, Prashanth W.; Orthmann, Steven; Schuch, Jona; Connor, Paula; Kaiser, Bernhard; Lerch, Martin; Driess, Matthias
Abstract: The scalable synthesis of phase‐pure crystalline manganese nitride (Mn3 N2 ) from a molecular precursor is reported. It acts as a superiorly active and durable electrocatalyst in the oxygen evolution reaction (OER) from water under alkaline conditions. While electrophoretically deposited Mn3 N2 on fluorine tin oxide (FTO) requires an overpotential of 390 mV, the latter is substantially decreased to merely 270 mV on nickel foam (NF) at a current density of 10 mA cm −2 with a durability of weeks. The high performance of this material is due to the rapid transformation of manganese sites at the surface of Mn3 N2 into an amorphous active MnO x overlayer under operation conditions intimately connected with metallic Mn3 N2, which increases the charge transfer from the active catalyst surface to the electrode substrates and thus outperforms the electrocatalytic activity in comparison to solely MnO x ‐based OER catalysts.